Parvifloron D-based potential therapy for glioblastoma: Inducing apoptosis via the mitochondria dependent pathway - Magalhães, Mariana; Domínguez-Martín, Eva María; Jorge, Joana; Gonçalves, Ana Cristina; Díaz-Lanza, Ana María; Manadas, Bruno; Efferth, Thomas; Rijo, Patrícia; Cabral, Célia (Frontiers in Pharmacology, 2022)
Glioblastoma (GBM) is the most malignant and frequent primary tumor of the central nervous system. The lack of diagnostic tools and the poor prognosis associated with this tumor type leads to restricted and limited options of treatment, namely surgical resection and radio-chemotherapy. However, despite these treatments, in almost all cases, patients experience relapse, leading to survival rates shorter than five years (~15-18 months after diagnosis). Novel therapeutic approaches are urgently required (either by discovering new medicines or by repurposing drugs) to surpass the limitations of conventional treatments and improve patients’ survival rate and quality of life. In the present work, we investigated the antitumor potential of parvifloron D (ParvD), a drug lead from natural origin, in a GBM cell line panel. This natural drug lead induced G2/M cell cycle arrest and apoptosis via activation of the intrinsic mitochondria-dependent pathway. Moreover, the necessary doses of ParvD to induce pronounced inhibitory effects were substantially lower than that of temozolomide (first-line treatment) required to promote comparable effects. Therefore, ParvD may have the potential to overcome the resistance related to TMZ and contribute to the pursuit of hopeful treatments based on ParvD as a drug lead for future chemotherapeutics.